Developing technological, pedagogical, and content knowledge (TPACK) booklet in biology subject to provide the TPACK materials for prospective biology teachers at UIN Sunan Kalijaga Yogyakarta - Utami, Aprillyana Dwi; Harahap, Guschairani; Khoiriyah, Alya Nur (Assimilation (Bandung), 2024)
This research aims to develop a valid and practical Technological, Pedagogical, and Content Knowledge (TPACK) booklet for biology subjects to provide the TPACK materials of Biology Education students, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta. This research is development research that carried out in three stages, namely the analysis, design, and evaluation stages. The analysis stage consists of literature study and identification needs. The design stage includes formulating objectives, preparing material, and designing the TPACK booklet for biological material. The evaluation stage itself is divided into self-evaluation, expert review, one-to-one and small group stages. This research was carried out only at the small group stage. The product research results were categorized as ‘very valid’ by the media validator with a score of 3.83 and the material validator with a score of 4. The development of the TPACK Booklet for biology subjects received a one-to-one and small group trial assessment with scores of 3.66 and 3.65 respectively in the ‘very practical’ category. It can be concluded that the TPACK Booklet for biology subjects is categorized as ‘very valid’ and ‘very practical’.